PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DI THE LANGHAM HOTEL JAKARTA - Nadya Fara Dilla; Surono Surono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research was conducted aiming to see the effect of product quality, service quality, and promotion on customer satisfaction at The Langham Hotel Jakarta. The population of this research are customers of The Langham Hotel Jakarta who have had a stay experience totaling 100 customers. The sampling technique used was purposive sampling and the number of samples was calculated using the Slovin formula. The study was conducted on 100 respondents using the Partial Least Square (PLS) analysis method with the SmartPLS 3 application. This research was conducted using quantitative and descriptive methods, describing the relationship between phenomena studied in a systematic, factual and accurate manner. positively but not significantly on customer satisfaction while for other variables namely service quality and promotion a positive and significant effect on customer satisfaction at The Langham Hotel Jakarta.